2019
DOI: 10.1111/1758-5899.12655
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of ‘Tax Spillover’: A New Multilateral Framework

Abstract: Tax spillovers are the effects one country's tax rules and practices have on other countries. They have been assessed in aggregate terms by the IMF using econometric models, and were found to have a ‘significant and sizable’ impact in reducing corporate tax bases and rates in ‘developing countries. However, a widely accepted form of country level spillover analysis remains elusive, despite demands from non‐governmental organisations (NGOs) and international organisations (IOs). We present the first framework f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The IMF's work also acknowledged methodological difficulties, with accurate country-level estimates being especially problematic using econometric equations (IMF, 2014: 15). In an effort to provide a foundation for assessing tax spillovers on a country-by-country basis we created a new spillover assessment tool kit (Baker and Murphy, 2019). Our framework moved beyond the IMF's work in five ways.…”
Section: Tax Spilloversmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMF's work also acknowledged methodological difficulties, with accurate country-level estimates being especially problematic using econometric equations (IMF, 2014: 15). In an effort to provide a foundation for assessing tax spillovers on a country-by-country basis we created a new spillover assessment tool kit (Baker and Murphy, 2019). Our framework moved beyond the IMF's work in five ways.…”
Section: Tax Spilloversmentioning
confidence: 99%
“…Any intellectual project with the aspiration of re-engineering global governance to prioritise alternative values and norms also needs to give serious consideration to the sets of conditions that make change plausible and achievable. In this contribution, we move beyond our recent work, which outlined the soft-law dynamics of a new spillover evaluation framework (Baker and Murphy, 2019), to establish more fully the political case for spillover assessments. We use literature on NGO benchmarking of revolutionary and reformist types to suggest that hybrid modes of working are often essential to increase political appeal and traction (Broome and Quirk, 2015a;Seabrooke and Wigan, 2015).…”
mentioning
confidence: 99%
“…Applying a spillover assessment tool kit in a full UK assessment, revealed that both capital gains and corporation tax provisions encouraged the shifting of income out of the income tax base (Baker and Murphy, 2019b: 5). At the same time, a whole range of exemptions, allowances and reliefs were found to provide favour to income earned from wealth rather than from work, further incentivising the under reporting of income (Baker and Murphy, 2019b: 4).…”
Section: Mmt Tax Allowances and Reliefs And The Implications For Uk mentioning
confidence: 99%
“…Applying a spillover assessment tool kit in a full UK assessment, revealed that both capital gains and corporation tax provisions encouraged the shifting of income out of the income tax base (Baker and Murphy, 2019b: 5). At the same time, a whole range of exemptions, allowances and reliefs were found to provide favour to income earned from wealth rather than from work, further incentivising the under reporting of income (Baker and Murphy, 2019b: 4). A recommendation emerging from that assessment was that all allowances and reliefs offered in the UK should be systematically evaluated to determine: their cost; their economic effectiveness; the benefits arising from continuing to offer them; and any impact of their withdrawal.…”
Section: Mmt Tax Allowances and Reliefs And The Implications For Uk mentioning
confidence: 99%
See 1 more Smart Citation